(untitled) (Journal of Surgical Sciences, 2019)
We report a case of Fascioliasis presented with recurrent cholangitis in a female necessitating multiple consultations and hospitalizations over a period of two years. Investigative profile failed to confirm any definite diagnosis prior to her admission in Hepato-Biliary-Pancreatic Surgery Division of the Department of Surgery of Bangabandhu Sheikh Mujib Medical University where she was provisionally diagnosed as a case suffering from extrahepatic cholagiocarcinoma. With the intent of extrahepatic excision with Rouxen-Y hepaticojejunostomy abdomen was explored and surprisingly 28 mature liver flukes (fasciola hepatica) were found lodged in the extra and intrahepatic biliary tree. Although fasciola hepatica infestation is more common in far East Asia, this case may represent the tip of an iceberg of endemic infestation of this trematode in Bangladesh which warrants further investigations. Journal of Surgical Sciences (2015) Vol. 19 (1) : 35-38